2019
DOI: 10.1021/acsnano.9b07020
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Collection Limit in Hot Electron Transistors with Ambipolar Hot Carrier Transport

Abstract: Hot electron transistors (HETs) containing two-dimensional (2D) materials promise great potential in high-frequency analog and digital applications. Here, we experimentally demonstrate all-2D van der Waals (vdW) HETs formed by graphene, hBN, and WSe2, in which the polarity of carriers could be tuned by changing bias conditions. We proposed a theoretical model to distinguish hot hole and hot electron components in the ambipolar vdW HET. Importantly, both hot hole and hot electron modes are achieved with pronoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…They achieved a high on-state current density ( J c ) of 1 Acm −2 . Similarly, Liu et al recently observed ambipolar HC transport for the first time in a newly proposed device architecture of a HET transistor for the efficient collection of HC 121 . The typical device structure consists of an extra thin (~1 nm) layer by layer stacking of graphene, hexagonal boron nitride and Tungsten diselenide.…”
Section: Plasmonic Hc and Their Applications In Other Optoelectronic Devicesmentioning
confidence: 76%
See 2 more Smart Citations
“…They achieved a high on-state current density ( J c ) of 1 Acm −2 . Similarly, Liu et al recently observed ambipolar HC transport for the first time in a newly proposed device architecture of a HET transistor for the efficient collection of HC 121 . The typical device structure consists of an extra thin (~1 nm) layer by layer stacking of graphene, hexagonal boron nitride and Tungsten diselenide.…”
Section: Plasmonic Hc and Their Applications In Other Optoelectronic Devicesmentioning
confidence: 76%
“…HC generation through plasmonic oscillation, especially by the interaction of LSP and the SPP, is a complex phenomenon. In a recent study, Shan et al 121 LSP and SPP that synergize to produce plasmonic HC. The electrons are excited by a 760-nm pump laser, and by crossing the Schottky barrier these electrons are injected into the MoS 2 layer where they are monitored by a probe pulse of 650 nm (Fig.…”
Section: Hc In Transistors and Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bending in the base-emitter barrier is faintly lowered by the increase of V CB , causing cold electron enhancements in device I E . A similar phenomenon can be seen in the type I device, as shown in Supporting Information Figure S6a–d and is also observed in a recent research . Once the device is operated in the fixed emitter current mode, α* will not deteriorate much as V CB increases (see Supporting Information Figure S8).…”
Section: Results and Discussionmentioning
confidence: 95%
“…This implies that the optimization of device parameters by careful selection of device materials can further improve the electrical properties of GHETs. Several studies then came after to demonstrate the use of other materials for the device’s base and insulating layers, such as 2D transition-metal dichalcogenides or h-BN, to enhance α and increase the current density of the device. More importantly, and in addition to all these, theoretical studies have speculated that GHETs have a potential for THz frequency operations. Since the device design employs the atomically thin graphene as the base material, injected electrons can flow ballistically through the base region, resulting in a faster transit time and better high-frequency performance.…”
mentioning
confidence: 99%